Cankarjevo tekmovanje v osnovni šoli - Saksida, Igor (Jezik in slovstvo, 2015)
After outlining the distinction between spontaneous and critical reading in the introduction, the article discusses the responses of primary school teachers gathered in a questionnaire related to an optional form of reading competence assessment known as the Cankar Award Contest: the role of mentors, the range and suitability of the literary texts, the essay titles and criteria for the assessment of pupils' answers. Critical reading is related to a communication approach to literature that defines "a reading event" as a transition from a subjective to a critical response to literature, a process in which the teacher's involvement is essential. Mentors of the Cankar Award Contest stress the importance of goals related to reading motivation and the development of reading competence, together with the individualisation of approaches to language teaching. When discussing classroom activities, they list critical reading of literary works, in-depth understanding of reading tasks and the topicalisation of literary messages as the most important components of a reading event. They find both reading tasks and reading criteria very appropriate; in their opinion, however, the criteria should be somewhat more precise at the first level of the contest.
Keywords: književnost; literature; osnovne šole; vloga mentorja; tekmovanja; bralna zmožnost; kritično branje